(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2014)
Milan is not only the golden location of the fashion and design industries as well as hightech research centres. What is peculiar about Milan, compared to London or Paris, is the contradiction between high density growth (made in the past by industry and the working class, today by finance and the creative class), and low polity. Milan is based on an external source of power corresponding to a weak nation-state. The local élites have been only partially able to negotiate with the central government. The past and recent history of Milan is one of fragmented urban expansion and limited vision. Here the urban contract is based on the (historically variable) social relationships and compromises between these main axial systems: infrastructures, knowledge, and creative industry. The first is representative of heavy capitalist and financial interests; the second is the expression of the intellectual capital of the city; the third has the flavour of the new emerging forces of the creative class. Analysing also some other Milan’s features it is clear that the urban contract is made of both local and global players in an asymmetric game.